Small Scale Fishers and CBD post 2020 Global Biodiversity Framework - Patel, Anna (WorldFish, 2023)
The negotiation for the Post 2020 Global Biodiversity Framework represents a potential threat for small scale fisher peoples. Increasing the number of protected areas by 30% by 2030 is a potential risk for SSF communities, whose lives belong and depend on these ecosystems. Conservation measures often exclude and displace SSF peoples and communities, with consequences for food security, livelihoods and the enjoyment of their human rights. The SSF Guidelines recognize that healthy ecosystems and their associated biodiversity are the fundamental basis for the livelihoods of marine and inland fishing communities and contribute to their overall well-being. This final webinar will look at SSF dependency to the integration of gender, traditional knowledge and human rights into the biodiversity frameworks from the lens of SSF Guidelines.